Factors related to antibiotic-associated diarrhea in patients in the intensive care unit receiving antifungals: a single-center retrospective study. Issue 5 (May 2019) - Jingjing, Sun; Yanshu, Zhang; Yu, Liu; Qindong, Shi; Xue, Wang; Lei, Zhang; Yingli, He; Litao, Guo
Objective: To analyze factors related to antibiotic-associated diarrhea (AAD) in patients in the intensive care unit (ICU) receiving antifungals with the aim of informing rational antibiotic use. Methods: Sex, age, medical history, use of proton pump inhibitors, administration of parenteral nutrition, albumin level, occurrence of AAD, type of antibiotics, duration of ICU admission, and prognosis were retrospectively analyzed. The associations of age, sex, medical history, and other factors with AAD were associated by logistic regression. Results: In total, 284 patients were enrolled (antifungals, n = 110; no antifungals, n = 174). The total incidence of AAD was 32.39%. The incidence of AAD was significantly different between the groups (52.73% vs. 19.54%). The duration of proton pump inhibitor therapy, duration of antifungal therapy, enzyme inhibitor antibiotic use, and azithromycin use were associated with AAD in ICU patients receiving antifungal therapy. The mean duration of ICU admission was higher in patients receiving antifungal therapy (20.14 ± 11.50 vs. 14.48 ± 8.54 days). There was no significant difference in ICU mortality rates. Conclusion: The duration of proton pump inhibitor therapy, duration of antifungal therapy, use of enzyme inhibitor antibiotics, and use of azithromycins were associated with AAD in ICU patients receiving antifungal therapy.